Financial Performance Index (FPIMS): a proposal to measure the performance and project execution capacity in manufacturing companies in Santander (COL) - Alfredo Enrique Sanabria-Ospino; Sandra Marcela Delgado-Ortiz; Nelson Antonio Moreno-Monsalve; William Stive Fajardo-Moreno (Dyna)
The manufacturing sector can be considered the main driver of economic growth in countries, as demonstrated by the macroeconomic variable GDP. However, during the pandemic, the historical rise in exchange rates and the increase in inflation and interest rates resulted in countries’ negative performance. Currently, Colombia ranks last in the world in terms of productivity among OECD member countries. This problem is reflected in the Santander region, where production and sales variables have experienced negative changes, in addition to a stagnation in employment in the manufacturing sector. The objective of this work is to design a financial composite index to measure competitiveness, in addition to analyzing its implications for measuring performance and the capacity to execute projects in manufacturing companies. For the development of the research, an index called FPIMS was estimated for 2392 companies. Correlational analysis was then carried out and the companies were categorized. Finally, machine learning models were used to predict the FPIMS value. The results show that the proposed index can be a useful tool to determine project execution capacity in manufacturing companies in Santander.